The Functional Anatomy of the Cornea and Anterior Chamber in Lampreys: Insights From the Pouched Lamprey, Geotria australis (Geotriidae, Agnatha) - Collin, H. Barry; Ratcliffe, Julian; Collin, Shaun P. (Frontiers in Neuroanatomy, 2021)
Extant lampreys (Petromyzontiformes) are one of two lineages of surviving jawless fishes or agnathans, and are therefore of critical importance to our understanding of vertebrate evolution. Anadromous lampreys undergo a protracted lifecycle, which includes metamorphosis from a larval ammocoete stage to an adult that moves between freshwater and saltwater with exposure to a range of lighting conditions. Previous studies have revealed that photoreception differs radically across the three extant families with the Pouched lamprey Geotria australis possessing a complex retina with the potential for pentachromacy. This study investigates the functional morphology of the cornea and anterior chamber of G. australis, which is specialised compared to its northern hemisphere counterparts. Using light microscopy, scanning and transmission electron microscopy and microcomputed tomography, the cornea is found to be split into a primary spectacle (dermal cornea) and a scleral cornea (continuous with the scleral eyecup), separated by a mucoid layer bounded on each side by a basement membrane. A number of other specialisations are described including mucin-secreting epithelial cells and microholes, four types of stromal sutures for the inhibition of stromal swelling, abundant anastomosing and branching of collagen lamellae, and a scleral endothelium bounded by basement membranes. The structure and function of the cornea including an annular and possibly a pectinate ligament and iris are discussed in the context of the evolution of the eye in vertebrates.